ChemInform Abstract: Nickel‐Catalyzed Borylation of Aryl Halides with 4, 4, 6‐Trimethyl‐1, 3, 2‐dioxaborinane. Issue 17 (4th April 2013) - Murata, Miki; Sogabe, Yosuke; Namikoshi, Takeshi; Watanabe, Shinji
Abstract Electron‐donating or ortho substituted aromatic bromides give low yields compared to the corresponding iodides (IIa) and (IId).